ANALISIS YURIDIS LARANGAN POLIGAMI DALAM AWIG-AWIG DESA PENGLIPURAN DITINJAU DARI UNDANG-UNDANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - Susetyo, Danny Trisno; Pradana, Aditya Fajri Kurnia; Sulistyowati, Herwin (AL HUKMU: Journal of Islamic Law and Economics, 2025)
This research discusses the analysis of the prohibition of polygamy in the awig-awig of Penglipuran Village in terms of the Marriage Law and the Compilation of Islamic Law. The purpose of this research is to identify the reasons behind the polygamy prohibition stated in the awig-awig of Penglipuran Village and to analyse its consistency with state law and Islamic teachings. The approach used in this research is normative empirical, by combining the study of existing laws and regulations and the reality of the application of customary norms in the field. The methods used included a literature study to analyse Law No. 1/1974 on Marriage, the Compilation of Islamic Law, and the text of the awig-awig of Penglipuran Village. In addition, field observations and interviews with traditional leaders and the local community were conducted to understand their perspectives on the prohibition of polygamy. The results show that the polygamy prohibition in the awig-awig of Penglipuran Village aims to maintain local social and cultural values that prioritise equality in marital relationships. However, this contradicts the provisions of state law which allows polygamy under certain conditions and Islamic law which provides leeway. The implication of this research is the importance of harmonisation between customary law, state law and religious teachings to create harmony in the norms prevailing in society.